A study of C60 via scanning probe microscopy, Hückel, and Monte Carlo methods - Leaf, J.M. (2017)
The C60 molecule, in a number of different environments and configurations, was studied via a range of theoretical and experimental techniques. Experimentally, scanning tunnelling microscopy (STM) and atomic force microscopy (AFM) techniques were employed to firstly study orientational ordering in C60 monolayers and multilayers, and subsequently, potassium doping of isolated C60 molecules, and C60 monolayers. A single C60 molecule was manipulated over successive K atoms, such that it is progressively doped, it was then studied via STM and AFM, where molecular charging was seen to influence both electronic structure and force characteristics. Two Monte Carlo simulations were written to investigate different aspects of C60 molecular kinetics on surfaces. The first is a novel simulation into the orientational ordering of C60 monolayers and multilayers, with the inclusion of a surface interaction. By pre-calculating a repulsive pairwise intermolecular interaction, using Hückel theory, hundreds of molecules in a molecular assembly could be efficiently simulated. Numerous complex monolayer and multilayer long range rotational configurations, as observed via STM from literature and our own experiments, were successfully modelled. A second Monte Carlo simulation was written to study the kinetics of a diffusing C60 on a hydrogen passivated silicon surface. This to estimate the feasibility of a future SPM recreation of the famous Maxwell’s Demon thought experiment. A Girifalco potential was applied from a number of static molecules to a sinusoidal surface potential. A Monte Carlo simulation was applied to this surface potential to fully explore the dynamics of the system. As a result, a number of optimal chamber configurations were suggested from outcomes observed in simulation.